Capsaicin Derivatives Containing Indole and Nitroindole for Improved Anti-Inflammatory Activity - Mukthung, Chaiyot; Chancharunee, Sirirat; Kielar, Filip; Pongcharoen, Sutatip; Wichai, Uthai (Asian Health, Science and Technology Reports, 2018)
In this investigation, capsaicin derivatives which containing indole or nitroindole in the tail region and a nitro group on the 4-hydroxybenzyl residue at the head region, were designed to mimic the benzyl residue at the terminal part of the daphnane diterpenoid moiety in resiniferatoxin (RTX). The novel capsaicin derivatives were readily synthesized using the peptide coupling reaction between heterocyclic acetic acid derivatives and benzylamine derivatives with moderate yield. Furthermore, novel capsaicin derivatives were evaluated for their ability to inhibit the production of tumor necrosis factor-alpha (TNF-alpha, one of the pro-inflammatory cytokines, by lipopolysaccharides (LPS)-stimulated human peripheral blood mononuclear cells (PBMCs) in which the transient receptor potential cation channel, subfamily V, member 1 (TRPV1) channel is present. It was found that capsaicin derivatives containing nitroindole in the tail region and a nitro group on the 4-hydroxybenzyl residue at the head region exhibited the highest activity for inhibition of TNF-alpha production, in comparison with capsaicin, giving reductions from 47.65%-51.95% and basis for this significant enhancement of the anti-inflammatory activity could potentially originate from the promotion of binding with TRPV1 on PBMCs through p-p stacking interactions provided from the nitrobenzylic and nitroindole residues at both ends.